Asteraceae da Serra de Ouro Branco, Minas Gerais, Brasil - Dias, Angelo Gervásio (2021)
The systematic treatment for Asteraceae (Angiospermae) was carried out in Serra de Ouro Branco in Minas Gerais, based on exsiccates deposited in Brazilian herbaria. This mountain range is located in the extreme south of the Espinhaço Range and the limit of the Quadrilátero Ferrífero, in addition to being located in a transition zone between the Cerrado and Atlantic Forest biomes. Its main physiognomy is that of a rupestrian field that is among the rural formations of the Cerrado Biome. Studies in phytophysiognomies of the Cerrado show that the Asteraceae family stands out among these grassland formations. In Serra de Ouro Branco, the Astereceae family is represented by 138 species in 58 genera, distributed in 15 tribes. The richest tribes in number of species are Eupatorieae (43 spp.), Vernonieae (33 spp.) and Astereae (22 spp.), the other tribes showed less than 7 spp. Among the tribes the most representative genera are Baccharis L. (18 spp.), Lessingianthus H.Rob. (13 spp.), Mikania Willd. (12 spp.) and Chromolaena DC. (9 spp.). Ten species are endemic to Minas Gerais, highlighting Aspilia duarteana JUSantos, which presents a degree of almost threatened, and Mikania pseudogracilis RMKing & H.Rob, which, in addition to being endemic to Minas Gerais, has endemism restricted to the iron quadrilateral and Cadeia do ridge. And presented 5 endangered species, and 3 near-threatened species. For the species of each tribe, taxonomic keys, taxonomic comments with flowering and fruiting data and illustrations of taxonomic characteristics are presented.